La dimensione performativa della vendetta e della rivalità nei Racconti di fate di D'Aulnoy, Lhérrtier e Perrault (Mantichora. Italian Journal of Performance Studies, 2020)
The literary fairy tale, from its birth in the French salonnes of the seventeenth century, became a privileged space for critical reflection on the performance and constructedness of the cultural categories of gender and identity. From the perspective of Judith Butler’s theory of gender performativity, the essay investigates the narrative strategies through which women fairy-tale writers Mme d’Aulnoy and Mlle Lhérititer contested the patriarchal constructions of gender identities. More specifically, the analysis of the motifs of vengeance and rivalry in their versions of the Cinderella theme (Finette Cendron and L’Adroite Princesse, ou Les Aventures de Finette) reveals how the early modern French women authors created a new type of heroine who redefined the notions of feminine and brought under scrutiny the masculine conceptions of gender difference and social roles.